2013
DOI: 10.1139/cjpp-2012-0456
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of hERG current and the disruption of trafficking as induced by roxithromycin

Abstract: Roxithromycin is an oral macrolide antibiotic agent that has been repeatedly reported to provoke excessive prolongation of the Q-T interval and torsades de pointes in clinical settings. To investigate the mechanisms underlying the arrhythmogenic side effects of roxithromycin, we studied the molecular mechanisms of roxithromycin on human ether-à-go-go-related gene (hERG) K(+) channels expressed in human embryonic kidney (HEK293) cells. Roxithromycin was found to inhibit wild-type (WT) hERG currents in a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Macrolides are known to bind and inhibit the hERG channels (alpha-subunits). In addition, roxithromycin inhibits hERG channels and disrupts hERG protein trafficking [ 93 ] (Table 3 ). No information was found on whether other macrolide antibiotics disrupt hERG channel trafficking.…”
Section: Non-antiarrhythmic Drugs Associated With Increased Risk Of Tmentioning
confidence: 99%
“…Macrolides are known to bind and inhibit the hERG channels (alpha-subunits). In addition, roxithromycin inhibits hERG channels and disrupts hERG protein trafficking [ 93 ] (Table 3 ). No information was found on whether other macrolide antibiotics disrupt hERG channel trafficking.…”
Section: Non-antiarrhythmic Drugs Associated With Increased Risk Of Tmentioning
confidence: 99%
“…In total, 1828 studies were retrieved from the literature search, of which, 97 (5%) were deemed eligible hERG/I Kr assays (Figure ). The characteristics of the eligible studies are detailed in Online Supplementary Table S3 . Eighty‐three (86%) of these studies provided IC50 values for at least 1 drug of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al found that mutations in drug-binding sites of the hERG channel could attenuate hERG current obstruction by roxithromycin, but did not significantly modify the disruption of trafficking [39]. According to Hancox et al study, D85N KCNE1 mutations demonstrated an increase in the sensitivity of IKr/hERG to inhibition with clarithromycin in vitro models [40].…”
Section: Original Articlementioning
confidence: 99%